2015
DOI: 10.1038/lsa.2015.95
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of photothermal phase signatures from arbitrary plasmonic nanoparticles and experimental verification

Abstract: We present a new approach for predicting spatial phase signals originating from photothermally excited metallic nanoparticles of arbitrary shapes and sizes. The heat emitted from such a nanoparticle affects the measured optical phase signal via changes in both the refractive index and thickness of the nanoparticle surroundings. Because these particles can be bio-functionalized to bind certain biological cell components, they can be used for biomedical imaging with molecular specificity, as new nanoscopy labels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 29 publications
1
35
0
1
Order By: Relevance
“…The TIP approach is appropriate as long as the relative change of of the permittivity, ∆ǫ m ∼ ∆T dǫ m /dT , is small. Typically, the thermo-derivative, dǫ m /dT , varies between ∼ 10 −5 / • K for standard dielectric materials [58] up to 10 −4 − 10 −3 / • K for water [59] or metals [60,61]. Thus, as long as the temperature increase (with respect to room temperature) is modest, i.e., limited to a few degrees, the change of the permittivity is indeed negligible.…”
Section: Self-consistent Calculation Of the Temperature In Metal Nanomentioning
confidence: 99%
“…The TIP approach is appropriate as long as the relative change of of the permittivity, ∆ǫ m ∼ ∆T dǫ m /dT , is small. Typically, the thermo-derivative, dǫ m /dT , varies between ∼ 10 −5 / • K for standard dielectric materials [58] up to 10 −4 − 10 −3 / • K for water [59] or metals [60,61]. Thus, as long as the temperature increase (with respect to room temperature) is modest, i.e., limited to a few degrees, the change of the permittivity is indeed negligible.…”
Section: Self-consistent Calculation Of the Temperature In Metal Nanomentioning
confidence: 99%
“…[30][31][32][33] It is also an available tool to observe bulk and interfacial electrical properties that cannot be directly observed, 34 such as the built-in voltage, doping concentration, diffusion time, and carrier mobility. [35][36][37][38][39] By modelling the impedance behavior to investigate the charge transport recombination mechanisms, it was found that there is efficient charge transfer between TiO 2 and the active layer, leading to improved electron mobility and energy level alignment for PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) have unique properties allowing applications in mechanics, catalysis, magnetism, optics, electricity, new material development, and heat physics, due to their morphology and size effects [1][2][3][4][5]. Among them, noble metal NPs have potential applications in the field of nanophotonics due to their strong nonlinear optical response, thus attracting significant attention [4][5][6][7][8]. As a typical representative of noble metals, silver nanoparticles (Ag NPs) are particularly prominent [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%